2020
DOI: 10.1088/1402-4896/ab3c3f
|View full text |Cite
|
Sign up to set email alerts
|

On the onset of entropy generation for a nanofluid with thermal radiation and gyrotactic microorganisms through 3D flows

Abstract: This work presents the entropy analysis of Maxwell nanofluid containing gyrotactic microorganism in the presence of homogeneous–heterogeneous reactions with modified heat and mass flux models. Modified models are presented by utilizing Cattaneo–Christov heat flux and generalized Fick’s law. Derived equations which shows the considered flow situation are modeled in the form of PDEs under boundary layer theory, then suitable transformation is applied to convert arising PDEs into a set of transformed ODEs which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(54 citation statements)
references
References 47 publications
1
53
0
Order By: Relevance
“…Defining the following expansions Using the series expansions in Equations (27)(28)(29)(30) in the Homotopy equations [see Equations (21) to 24], we get the set of linear differential equations, after comparing the powers of ζ . By applying the property of Homotopy perturbation method, i.e., ζ → 1, we get…”
Section: Series Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining the following expansions Using the series expansions in Equations (27)(28)(29)(30) in the Homotopy equations [see Equations (21) to 24], we get the set of linear differential equations, after comparing the powers of ζ . By applying the property of Homotopy perturbation method, i.e., ζ → 1, we get…”
Section: Series Solutionsmentioning
confidence: 99%
“…Chakraborty et al [25] researched the extrinsic magnetic influence and bioconvection flow with nanoparticles with convective boundary conditions. Few important studies on the motile gyrotactic microorganisms and nanofluids can be found in Shahid et al [26], Waqas et al [27], Waqas et al [28], and Sohail et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…Akbar [9] investigated the bio-convection peristaltic convection of nanofluid in a given asymmetric channel saturated with gyrotactic micro-organisms. Mabood et al [10] reported a free convective flow of non-Newtonian-type nanofluids (see for example [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] to understand the term non-Newtonian nanofluids) in permeable medium saturated with gyrotactic-type micro-organisms.…”
Section: Introductionmentioning
confidence: 99%
“…This (MHD) phenomena was investigated when the nano fluid is electrically conductive in micro annuli [31]. M. Sohail et al [32] analysis the entropy relative a Maxwell nano fluid by modifying the heat and mass transfer models. Also, the generalize the law of Fick.…”
Section: Introductionmentioning
confidence: 99%